PENGARUH PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP PEMBANGUNAN PERTANIAN DI KABUPATEN KONAWE - Risnawati Risnawati; Weka Widayati; La Ode Muh. Magribi (Jurnal Perencanaan Wilayah, 2019)
This research were conducted to 1) Know about the construction of road infrastructure in Konawe Regency. 2) Know about the agricultural development in Konawe Regency. 3) Know the effect of road infrastructure on agricultural development in Konawe Regency. This research was descriptive qualitative and quantitative. The variables of this research, in this case were road infrastructure variables include road length, accessibility. While agricultural development included land area, agricultural production, inputs, harvest / post-harvest and marketing. Based on the results of the study can be concluded that from 9 sub-districts in Konawe Regency, Abuki, Anggaberi, Konawe, Meluhu, Tongauna, Uepai, Unaaha, Wawotobi, and Wonggeduku Subdistricts the road construction has increased since the last 5 years. In 2014 the road length was 960.25 Km and 2018 amounted to 115.61 Km. For the opening of new road, the focus was on the business route using the village budget. Agricultural development in Konawe Regency, especially in the location where the research was conducted, has increased, marked by a large number of road infrastructure developments from 2014-2018, where most of the road infrastructure development has been carried out in agricultural centers.This had an impact on the increasing use of agricultural land from the last 5 years (2014-2018) as well as the increase in agricultural production in Konawe district, specifically 9 Subdistricts of the Research Area. The use of agricultural land in the study site consisted of 3 types of land use, i.e Farm, rice fields and dry land. Keywords: Road infrastructure and agricultural development